Covered girls - Mclntyre, Janet; Wendel, Amy; Learning Media (New York : Filmakers library, 2002)
This film documents the daily experience of Muslim -American teenage girls in New York and their challenge.
Keywords: Women, Muslim -- Conduct of life -- United States